Theory, practice and performance. Issue 1 (2nd January 2017) - Gallagher, Shaun
ABSTRACT: I focus on the enactivist and extended mind approaches to embodied cognition (EC), and specifically on the concepts of body schema, affectivity, distributed cognition and intersubjectivity to show how EC has relevance to questions about expert performance, and to the theory and practice of performing arts.